Development of an Information System Based in Electronic Health Record to Support Decision Making in Emergency Rooms (2004)
ABSTRACT: Emergency rooms services are places where, day by day, vital decision are taken, such that can represent success or failure, just with a thin line of separation. There are many factors described that can affect the capacity of decision-making and giving support to this process is essential. Historically information systems had been so expensive especially in the development, fortunately today there are a lot of open source – free distribution tools to support this kind of proposals. The axis of a clinical information system to support decisions is the medical record in self. An EHR was developed with interface Web Browser orientation seeking dynamic behaviour. We used PHP was as base language, with some support of javascript and MySQL as Data Base Management system. A “transactional model” was implemented where there is a definition about clinical data to be collected named as “events”, which are in charge of control the data behaviour. It was possible to identify 375 single events. Each event is classified in one of nine types of event according with how data are collected and showed. Is this order of ideas a health record is a set of transactions or events stored chronologically from which is possible to reconstruct all the patient history. There is a set of tables that supports the “knowledge” of system that includes vademecum, CIE-10 (ICD-10), handling guidelines, among others. The system is data driven focused in initial form, diagnosis and order entry. Then there is an informatics tool that can be released under GNU license, able to handle clinical data from patients in an emergency room, and adaptable potentially to any kind on place depending of definitions made in transactional model. That incorporates alerts to errors, helps to orient the physician and presents alternatives to be followed contextualized.